INCLUSIVE PHYSICAL EDUCATION: DIFFICULTIES OF ACADEMICS IN INTERNSHIP INTERVENTION (Fiep Bulletin - online, 2025)
Introduction: Inclusive Physical Education has encountered many barriers since its conception in the mid-1990s. In view of this factor, Physical Education interns increasingly need efforts to be able to include students with disabilities, in order to carry out inclusive proposals. Objective: Thus, the present research had as a general objective to identify if there are difficulties among Physical Education interns at the State University of Piauí of the Dr. Josefina Demes Campus in including students with disabilities in their classes. Methods: The participants of the research were students enrolled in block VIII of the Physical Education Degree course at the State University of Piauí, the sample was limited only to Physical Education students who had internship experience within the scope of the theme investigated by this study. The data analysis was based on Bardin's structuring. Results: the figures present students' reports in terms of difficulties, as well as strategies used to include students with disabilities in physical education classes. Conclusion: it was possible to discover with the reports that there are difficulties in including students with disabilities in their Physical Education classes and that there are different problems faced, whether it is a lack of adequate training, lack of resources and support, or physical and structural barriers.
Keywords: School Inclusion; People with disabilities; Physical Education; Supervised Curricular Internship